The Productivity Slowdown and the Declining Labor Share: A Neoclassical Exploration - Gene Grossman; Elhanan Helpman; Ezra Oberfield; Thomas Sampson (Center for Economic Studies and ifo Institute (CESifo), 2017)
We explore the possibility that a global productivity slowdown is responsible for the widespread decline in the labor share of national income. In a neoclassical growth model with endogenous human capital accumulation à la Ben Porath (1967) and capital-skill complementarity à la Grossman et al. (2017), the steady-state labor share is positively correlated with the rates of capital-augmenting and labor-augmenting technological progress. We calibrate the key parameters describing the balanced growth path to U.S. data for the early postwar period and find that a one percentage point slowdown in the growth rate of per capita income can account for between one half and all of the observed decline in the U.S. labor share.
Keywords: O40; 330; neoclassical growth; balanced growth; technological progress; capital-skill complementarity; labor share; capital share